Demonstrating advanced U-space services for urban air mobility in a co-simulation environment - Fremond, Rodolphe; Tang, Yiwen; Bhundoo, Prithiviraj; Su, Yu; Tutku, Arinc; Xu, Yan; Inalhan, Gokhan (Cranfield University, 2022)
The present paper formalises the development of a co-simulation environment aimed at demonstrating a number of advanced U-space services for the Air Mobility Urban - Large Experimental Demonstrations (AMU-LED) project. The environment has a visionary build that addresses Urban Air Mobility (UAM) challenges to support the High/Standard Performance Vehicles (HPV/SPV) operations within a complex urban environment by proposing an integrated solution that packages advanced services from the pre-flight to the in-flight phase in line with ongoing UAM Concept of Operations (ConOps). This setup opts for a holistic approach by promoting intelligent algorithmic design, artificial intelligence, robust serviceability through either virtual and live elements, and strong cooperation between the different services integrated, in addition to sustain interoperability with external U-space Service providers (USSP), Common Information Service providers (CISPs), and Air Traffic Controllers. The prototype has been recently showcased through the AMU-LED Cranfield (UK) demonstration activities.
https://whova.com/xems/whova_backend/get_event_s3_file_api/?event_id=sesar_202212&file_url=https://d1keuthy5s86c8.cloudfront.net/static/ems/upload/files/1670053372_jdpqz_SIDs_2022_paper_112_final_r.pdf&eventkey=4c68ac23dcb73ce4b5be87ca1b5b0ccaed6016dfcefe0c4b6af300caca061224